1998
DOI: 10.1016/s0014-5793(98)00869-2
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C inhibitors stimulate arachidonic and docosahexaenoic acids release from uterine stromal cells through a Ca2+‐independent pathway

Abstract: The mechanisms underlying arachidonic acid (AA) release by uterine stromal (U sss ) cells were studied. Stimulation of AA release by calcium ionophore and PMA are inhibited by various PKC inhibitors and by calcium deprivation. These results suggest the involvement of an AA-specific cPLA P as the release of docosahexaenoic acid (DHA) from prelabelled cells is much lower than the release of AA. The results also show a more original stimulation of AA and DHA release induced by PKC inhibitors, which is insensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…We recorded the exudate volume at 2 h after inflammation (0.47 Ϯ 0.02 ml) and estimated that the exudate levels of unesterified DHA, EPA, and AA were 141, 172, and 218 nM, respectively, and may reflect stimulated release of EPA and DHA from lipid storage sites. The early involvement of iPLA 2 , a calcium-insensitive phospholipase A 2 that can release DHA (33), in AA release was recently demonstrated in acute pleural inflammation (34). In this respect, we found via proteomic analysis that S100A9, a known AA-binding protein (35), was present in the exudate within 2 h after initiation of inflammation and reached maximal at the onset of R i , paralleling the PMN infiltration time course (Figs.…”
Section: Discussionsupporting
confidence: 55%
“…We recorded the exudate volume at 2 h after inflammation (0.47 Ϯ 0.02 ml) and estimated that the exudate levels of unesterified DHA, EPA, and AA were 141, 172, and 218 nM, respectively, and may reflect stimulated release of EPA and DHA from lipid storage sites. The early involvement of iPLA 2 , a calcium-insensitive phospholipase A 2 that can release DHA (33), in AA release was recently demonstrated in acute pleural inflammation (34). In this respect, we found via proteomic analysis that S100A9, a known AA-binding protein (35), was present in the exudate within 2 h after initiation of inflammation and reached maximal at the onset of R i , paralleling the PMN infiltration time course (Figs.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, preincubation of cells with 50 M BEL for 30 min, a very effective concentration to inhibit iPLA 2 activity (Table 2), caused a significant decreased release of [ (Table 1). This is consistent with previous results suggesting the participation of a BEL-insensitive iPLA 2 to this mechanism (17). The presence of both BEL-sensitive and -insensitive iPLA 2, demonstrated in bovine brain (28,29), has still to be formally established in U III cells and the regulatory mechanism of these enzymes by PKC should be clarified.…”
Section: Effect Of H 2 O 2 On Aa Esterification Into Phospholipidssupporting
confidence: 92%
“…Indeed, enhanced basal and H 2 O 2 responses were observed after exposure to AA-COCF 3 (ϩ65% and ϩ56%, respectively, Table 1 (Fig. 1, right panel), arguing against the involvement of cPLA 2 , as this enzyme hardly releases DHA compared to AA (17,26).…”
Section: Effect Of H 2 O 2 On Aa Release: Role Of Pkc and Calciummentioning
confidence: 92%
See 1 more Smart Citation
“…Recent studies from our group have shown that a Ca 2+ ‐independent PLA 2 enzyme is responsible for basal release of AA and docosahexaenoic acid (DHA) in unstimulated rat uterine stromal (U III ) cells [30]. We also found a specific pattern for AA and DHA distribution within phospholipid classes of these cells [31].…”
mentioning
confidence: 56%